Out of the classroom lessons of science and social studies - Ljiljana B. Mitić; Valentina M. Zlatanović Marković (University of Belgrade, Teacher Education Faculty, 2023)
The paper offers a critical analysis of the basic characteristics, as well as didacticmethodological values and shortcomings of the out of the classroom lessons of Science and Social Studies. The goal of the analysis is to discover the possibilities that this type of teaching and learning provides in the operationalization of the goals and outcomes of the teaching content of this school subject and other teaching content, especially in terms of two types of classroom teaching: school in nature and ambiental teaching. Although these are two different types of educational work, both school in nature and ambiental teaching, if wellplanned and professionally implemented, offer numerous opportunities in all phases of the teaching process. The ultimate goal is the mental engagement of students as an indicator of quality teaching.